Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Objective The ISG-STS 1001 was an international, randomized, phase III, trial for localized, high-risk, STS comparing neoadjuvant ChT with epirubicin and ifosfamide (EI) versus a histology-tailored regimen. The trial included also a cohort of patients not randomized but just registered and treated with EI. Herein, we analyzed tolerability and activity of concurrent EI and RT in the ISG-STS 1001. Methods and patients EI was made up of epirubicin 120 mg/m² plus ifosfamide 9 g/m² per cycle. RT was delivered at a dose of 44-50 Gy pre-operatively or 60-66 Gy post-operatively. ChT dose-intensity (DI), grade ≥3 hematological toxicities, acute RT-related toxicities, post-operative local complications, and radiological response by RECIST were compared between the group of patients receiving concurrent pre-operative ChT and RT (ChT/RT group) and the group receiving pre-operative ChT alone (ChT group). Results Among the 548 patients enrolled in the ISG-STS 1001, 287 were included in the current analysis (146 received pre-operative RT). Median ChT DI was >90% in both groups. Hematological toxicities were comparable between the two groups. Concerning post-operative complications, a higher number of wound dehiscence (9% vs 3.5%, respectively, p = 0.06) and seroma (10.4% vs 2.8%, respectively, p = 0.01) were observed in the ChT/RT group compared to the ChT group. A statistically significant association between RECIST response and pre-operative RT was found (20.3% and 9.8% in the ChT/RT group and in the ChT group, respectively, p = 0.02). Conclusions Concurrent EI and RT is feasible and safe, resulting in increased proportion of dimensional responses.